Assessing the role of financial development and financial inclusion to enhance environmental sustainability: Do financial inclusion and eco-innovation promote sustainable development? - Wang, Yaping; Fahad, Shah; Wei, Liqian; Luo, Bowen; Luo, Jianchao (Frontiers in Environmental Science, 2022)
In the context of increasing uncertainty in the international economic environment and changes in the labor market, it is imperative to pay proper attention to the environmental quality and sustainability. This paper theoretically analyzes the impact of financial development and financial inclusion on the environmental sustainability. Based on the survey data of 2093 households in Xunyi and Yangling, Shaanxi Province, China, the 2SLS model, and the instrumental variable quantile regression model are constructed to test the association of variables. The results show that the development of financial inclusion and financial development have an inverted “U” shaped nonlinear effect on the environmental quality and efficiency; Only after the development of financial inclusion reaches a certain degree can the environmental quality and sustainability be effectively improved. The results of the quantile regression of instrumental variables show that financial inclusion significantly improves the environmental quality with medium and high degrees but does not have a significant effect on the environmental quality and sustainability with low degrees. After considering the endogeneity and robustness test, the above conclusion still holds. Further research shows that inclusive financial development improves environmental quality and results in sustainable development. Improving the convenience and depth of use of financial services is the key to effectively reducing rural household economic vulnerability and improve the environmental quality. The heterogeneity analysis shows that financial inclusion development has a stronger effect on improving the environmental quality. This study provides empirical evidence and policy implications to better promote financial inclusion to improve the economic vulnerability of rural households, improve environmental quality and achieve the sustainable development. These findings provide policy support to better promote financial inclusion to improve the economic vulnerability of rural households, improve environmental quality and achieve the sustainable development, which can ameliorate environmental degradation, and create a safe, healthy and sustainable environment for achieving sustainable development goals.